2022
DOI: 10.3389/fpsyt.2022.928076
|View full text |Cite
|
Sign up to set email alerts
|

Does urinary metabolite signature act as a biomarker of post-stroke depression?

Abstract: BackgroundIt is difficult to conduct the precise diagnosis of post-stroke depression (PSD) in clinical practice due to the complex psychopathology of depressive disorder. Several studies showed that gas chromatography–mass spectrometry (GC-MS)-identified urinary metabolite biomarkers could significantly discriminate PSD from stroke survivors.MethodsA systematic review was performed for the keywords of “urinary metabolite” and “PSD” using Medline, Cochrane Library, Embase, Web of Science, PsycINFO, Wanfang, CNK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Due to the high reproducibility of electron ionization in MS, GC-MS can utilize many mass spectra libraries, which enables relatively easy identification of peaks. Several studies have shown that urinary metabolite biomarkers identified by GC-MS can identify post-stroke depression (PSD) in stroke survivors [17]. A biomarker panel consisting of glyceric acid, tyrosine, and azelaic acid was identified in middle-aged and elderly patients with PSD [18,19].…”
Section: Gc-msmentioning
confidence: 99%
“…Due to the high reproducibility of electron ionization in MS, GC-MS can utilize many mass spectra libraries, which enables relatively easy identification of peaks. Several studies have shown that urinary metabolite biomarkers identified by GC-MS can identify post-stroke depression (PSD) in stroke survivors [17]. A biomarker panel consisting of glyceric acid, tyrosine, and azelaic acid was identified in middle-aged and elderly patients with PSD [18,19].…”
Section: Gc-msmentioning
confidence: 99%
“…A systematic review showed that differential urinary metabolites detected by gas chromatography–mass spectrometry (GC-MS) had good potential for the differentiation of PSD. 25 One plasma metabolomic study based on liquid chromatography–mass spectrometry (LC-MS) showed that amino acid metabolism, lipid metabolism and oxidative stress were associated with PSD. 26 Another plasma metabolomic study based on proton nuclear magnetic resonance ( 1 H-NMR) indicated that disorders of neurotransmitter levels and oxidative stress were involved in the initiation of PSD.…”
Section: Introductionmentioning
confidence: 99%